L’Italia, la Slovacchia e l’Europa. Un percorso storico comune - Minuto Rizzo, Alessandro (Rivista di studi politici internazionali, 2010)
Europe is revisiting itself after the divisions of the cold war and centuries of internal fights. It is an extraordinary result we Europeans should be proud of. It allows us to see currents of history and common features that were not easy to detect when wars and tensions were the focus of attention. The relations between Italy and Slovakia are a good example as we discover that the two peoples have much in common and developed solid bonds along the centuries. We started with Marcus Aurelius, the famous emperor and philosopher who found inspiration and wrote his meditations in this region, then at the borders of the empire. The Saints Cyrillus and Methodius, protectors of Europe, evangelized Slovakia and are buried in Rome, a natural bond. During the 19th century oppressed nationalities fought all along the continent to regain their identities. Italians and Slovaks were at the forefront of those movements and we know that there were frequent contacts and reciprocal sympathy. During the first world war Italy strongly supported the Slovak national movement and the first unit of the new Slovak army was constituted in Rome in spring 1918. The Italian government hosted with sympathy and practical assistance Mr. Sˇtefanik, the father of modern Slovakia. Then came the tormented history of the second world war. More recently, during the cold war Italy did its best to show solidarity to those who were victims of the regime. The university of Bologna was the first to give a laurea honoris causa to Alexander Dubcek in 1988. This brief excursus through history does not take into account direct migrations, culture and arts. Altough different from each other, Italy and Slovakia share a natural interest to networking with other peoples, to belonging to a larger space, to working and trading within common rules. The European union is the natural conclusion of this process. It is in the common interest for the two countries to work together in this framework as best as they can. The first objective is to aim at a good functioning of the European system, while at the same time developing common projects for the mutual benefit. L’Europe se revisite après les divisions de la guerre froide et des siècles de luttes internes. C’est un résultat extraordinaire dont nous européens devrions être fières. Cela nous a permis de comprendre des faits historique et de voir des traits communs qui n’étaient pas facile à détecter quand guerres et tensions focalisaient notre attention. L’Italie et la Slovaquie sont un bon exemple car nous découvrons que les deux peuples ont beaucoup en commun et ont développé des liens très solides le long des siècles. Nous commençâmes tout d’abord par Marc Aurèle, le fameux empereur et philosophe qui trouva son inspiration et a écrivit ses « Pensées » dans cette région, qui à l’époque se trouvait aux limites de l’empire. Les saints Cyrille et Méthode, protecteurs d’Europe, ont évangélisé la Slovaquie et sont enterrés à Rome, un lien naturel. Pendant le 19ème siècle les nationalités opprimées ont combattu tout au long du continent pour regagner leurs identités. Les italiens et les slovaques étaient en tête à ces mouvements et nous savons qu’il y avait des contacts fréquents et une sympathie réciproque. Pendant la première guerre mondiale l’Italie a fortement soutenu le mouvement national. La première unité de la nouvelle armée slovaque a été constituée à Rome au printemps 1918. Le gouvernement italien a accueilli et assisté à M. Stepanik, le père de la Slovaquie moderne. Après cela est venue l’histoire tourmentée de la seconde guerre mondiale. Plus récemment, pendant la guerre froide, l’Italie a fait de son mieux pour démontrer sa solidarité envers ceux qui étaient victimes du régime. L’Université de Bologne était la première à donner une maîtrise honoris causa à Alexander Dubcek en 1988. Ce bref récit historique ne tient pas compte de l’émigration directe, la culture et les arts. Malgré leurs différences ces deux nations partagent un intérêt naturel vers les autres peuples, la volonté d’appartenir à un espace plus large, de travailler et de commercer avec des règles communes. L’Union européenne est la conclusion naturelle de ce processus. C’est dans l’intérêt de chacun que les deux pays travaillent ensemble dans ce cadre le mieux possible. Le premier objectif est celui de faire de façon que le système européen fonctionne bien et en même temps que des projets communs soient développés au bénéfice mutuel PAROLE CHIAVE: Unione europea; Santi Cirillo e Metodio; Alexander Dubcek; Milan Sˇtefanik; Nazionalità oppresse